A Fluorination/Aryl Migration/Cyclization Cascade for the Metal‐Free Synthesis of Fluoro‐Benzoxazepines. Issue 11 (23rd December 2015) - Ulmer, Anna; Brunner, Christoph; Arnold, Andreas M.; Pöthig, Alexander; Gulder, Tanja
Abstract: Fluorinated organic molecules are of high interest for many applications across chemical and medical disciplines. Efficient methods for the synthesis of such compounds are thus needed. Within this work, application of the bench‐stable cyclic hypervalent iodine(III) fluoro reagent1 facilitated the development of an efficient, metal‐free method for the preparation of the novel class of 4‐fluoro‐1, 3‐benzoxazepines starting from readily available styrenes. The efficacy and broad applicability of this concept is demonstrated by the synthesis of 20 structurally diverse congeners in high yields, regio‐, and diastereoselectivities. The presented method provides complementary chemoselectivity when compared to the common, commercially available electrophilic fluorination reagents, such as selectfluor. First mechanistic investigations with isotopically labeled substrates reveal a complex reaction mechanism, proceeding via an unusual fluorination/1, 2‐aryl migration/cyclization cascade. Abstract : Starting from styrenes, an easy‐to‐handle, metal‐free and efficient synthesis of the structurally novel 4‐fluoro‐1, 3‐benzoxazepines was established using fluoroiodane1 . This transformation exhibits a complementary chemoselectivity when compared to other electrophilic F ‐transfer reagents and proceeds via a fluorination/1, 2‐aryl migration/cyclization cascade.